Microbial Culture in Minimal Medium With Oil Favors Enrichment of Biosurfactant Producing Genes - Araújo, W. J.; Oliveira, J. S.; Araújo, S. C. S.; Minnicelli, C. F.; Silva-Portela, R. C. B.; da Fonseca, M. M. B.; Freitas, J. F.; Silva-Barbalho, K. K.; Napp, A. P.; Pereira, J. E. S.; Peralba, M. C. R.; Passaglia, L. M. P.; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
The waste produced by petrochemical industries has a significant environmental impact. Biotechnological approaches offer promising alternatives for waste treatment in a sustainable and environment-friendly manner. Microbial consortia potentially clean up the wastes through degradation of hydrocarbons using biosurfactants as adjuvants. In this work, microbial consortia were obtained from a production water (PW) sample from a Brazilian oil reservoir using enrichment and selection approaches in the presence of oil as carbon source. A consortium was obtained using Bushnell-Haas (BH) mineral medium with petroleum. In parallel, another consortium was obtained in yeast extract peptone dextrose (YPD)-rich medium and was subsequently compared to the BH mineral medium with petroleum. Metagenomic sequencing of these microbial communities showed that the BH consortium was less diverse and predominantly composed of Brevibacillus genus members, while the YPD consortium was taxonomically more diverse. Functional annotation revealed that the BH consortium was enriched with genes involved in biosurfactant synthesis, while the YPD consortium presented higher abundance of hydrocarbon degradation genes. The comparison of these two consortia against consortia available in public databases confirmed the enrichment of biosurfactant genes in the BH consortium. Functional assays showed that the BH consortium exhibits high cellular hydrophobicity and formation of stable emulsions, suggesting that oil uptake by microorganisms might be favored by biosurfactants. In contrast, the YPD consortium was more efficient than the BH consortium in reducing interfacial tension. Despite the genetic differences between the consortia, analysis by a gas chromatography-flame ionization detector showed few significant differences regarding the hydrocarbon degradation rates. Specifically, the YPD consortium presented higher degradation rates of C12 to C14 alkanes, while the BH consortium showed a significant increase in the degradation of some polycyclic aromatic hydrocarbons (PAHs. These data suggest that the enrichment of biosurfactant genes in the BH consortium could promote efficient hydrocarbon degradation, despite its lower taxonomical diversity compared to the consortium enriched in YPD medium. Together, these results showed that cultivation in a minimal medium supplemented with oil was an efficient strategy in selecting biosurfactant-producing microorganisms and highlighted the biotechnological potential of these bacterial consortia in waste treatment and bioremediation of impacted areas.